Effectiveness of Bupropion and Varenicline for Smokers With Baseline Depressive Symptoms. Issue 5 (15th December 2022) - Zhang, Helena; Gilbert, Emily; Hussain, Sarwar; Veldhuizen, Scott; Le Foll, Bernard; Selby, Peter; Zawertailo, Laurie
Abstract: Introduction: Smokers with concurrent depression are less likely to achieve abstinence, even with pharmacotherapy. The purpose of this secondary data analysis was to evaluate if the presence of any depressive symptoms at baseline alters the effectiveness of bupropion and varenicline for smoking cessation. Aims and Methods: Eligible participants were enrolled via the internet and randomized 1:1 to receive a 12-week supply of either bupropion ( n = 465) or varenicline ( n = 499). Depressive symptoms were assessed using the Patient Health Questionnaire (PHQ-2). Follow-up surveys were conducted at weeks 4, 8, 12, 26, and 52 to assess self-reported quit. The primary outcome was 7-day point prevalence abstinence at 12 weeks follow-up (end-of-treatment). Results: Participants who endorsed any depressive symptoms (PHQ-2 > 0; n = 280) were less likely to be quit at end-of-treatment compared to participants who did not endorse any symptoms (PHQ-2 = 0; n = 684) (OR = 0.56, 95% CI: 0.38 to 0.8, p = .003). Within the varenicline group, quit outcomes did not differ between those with and without depressive symptoms (21.3% vs. 26.9%, respectively). Within the bupropion group, however, those with symptoms had a significantly reduced quit rate compared to those without symptoms (7.0% vs. 17.3%, respectively). Conclusions: The presence of even one symptom of depression at the start of a quit attempt may adversely affect quit outcomes. Patients should be assessed for depressive symptoms when planning to quit smoking as it may inform the approach to treatment. However, future studies are needed to confirm these findings. Implications: Findings from the current study illustrate the importance of evaluating baseline sub-clinical depressive symptoms before a quit attempt using first-line pharmacotherapies. This secondary analysis of a large-scale randomized trial suggests that bupropion may be less effective for those with baseline depressive symptoms while varenicline may be equally effective for those with and without depressive symptoms